Housing shortage for low-income in Yemen : causes and suggestions. - Alaghbari, Wa'el; Salim, Azizah; Dola, Kamariah; Abang Ali, Abang Abdullah (Emerald Group Publishing Limited, 2009)
Purpose – The purpose of this paper is to identify the factors that cause housing shortage for lowincome groups in Yemen and recommend some solutions to alleviate the problem. Design/methodology/approach – A questionnaire survey has been used as the tool to carry out this study. The first part of the questionnaire consisted of three groups namely: economic, administrative, and legal factors. The second part consists of suggestions on housing supply, construction methods, and materials used for low-cost housing in Yemen. The level of importance of the categories was measured and the relative importance of weightage was ranked. Findings – The results show that the most important economic factors causing housing shortage were poor handling of available economic resources and shortage of economic resources. The most important administrative factors causing housing shortage were lack of organization and synchronization and not conducting studies on housing. The most important legal factor causing housing shortage was lack of legalization of housing. Originality/value – The findings could be used to improve housing policies and strategy in Yemen in order to decrease the housing shortage, particularly for the low-income group. Keywords Housing, Low pay, Disadvantaged groups, Yemen Paper type Research paper